2020
DOI: 10.3390/pharmaceutics12040392
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid-In-Oil Microemulsions Prepared with Biocompatible Choline Carboxylic Acids for Improving the Transdermal Delivery of a Sparingly Soluble Drug

Abstract: The transdermal delivery of sparingly soluble drugs is challenging due to of the need for a drug carrier. In the past few decades, ionic liquid (IL)-in-oil microemulsions (IL/O MEs) have been developed as potential carriers. By focusing on biocompatibility, we report on an IL/O ME that is designed to enhance the solubility and transdermal delivery of the sparingly soluble drug, acyclovir. The prepared MEs were composed of a hydrophilic IL (choline formate, choline lactate, or choline propionate) as the non-aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 47 publications
3
78
0
Order By: Relevance
“…Islam et al [ 47 ] developed a series of microemulsions with acyclovir and ionic liquid (choline oleate) to evaluate in vitro the permeation of acyclovir through the skin. The results obtained by those researchers revealed that the acyclovir permeation was intensified by using the ionic liquid.…”
Section: Discussionmentioning
confidence: 99%
“…Islam et al [ 47 ] developed a series of microemulsions with acyclovir and ionic liquid (choline oleate) to evaluate in vitro the permeation of acyclovir through the skin. The results obtained by those researchers revealed that the acyclovir permeation was intensified by using the ionic liquid.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors are involved in the penetration of the skin by DPS-2 carried within the oil core of the developed O/W microemulsion: (1) the low surface tension of the microemulsion, and, consequently, the close and prolonged contact with the skin, ensuring high concentration gradient for drug skin uptake; (2) the improved penetration of the microemulsion into the hair follicles, leading to improved delivery into viable skin layers (epidermis and/or dermis); (3) the perturbation of SC lipid matrix by interactions of the microemulsion’s components with the SC, leading to improved permeability through the SC lipid bilayers [ 59 ]. Actually, numerous studies have recently confirmed that, owing to relatively high surfactant concentration, microemulsions lead to alterations in skin barrier function, such as the disruption of intercellular regions of SC, due to the fluidization and/or extraction of the SC lipid matrix [ 61 , 62 , 63 ]. Dermal irritation is one of the most common adverse effects when applying formulations topically, therefore, when developing novel topical formulations, apart from efficacy, the assessment of the dermal irritation potential is a critical factor.…”
Section: Discussionmentioning
confidence: 99%
“…Microemulsions are thermodynamically stable colloidal mixtures of two immiscible liquids (i.e., water and oil) stabilized by surfactant molecules [73]. ILs proved to be promising alternatives to these components, being able to replace oil, water, and surfactant phases (Figure 2), improving the delivery of APIs across biological membranes [74,75].…”
Section: Ils As Permeation Enhancers and Microemulsion Components For Drug Deliverymentioning
confidence: 99%